A Comment on the Economics of Labor Adjustment: Mind the Gap: Evidence from a Monte Carlo Experiment: Reply - Cooper, Russell; Willis, Jonathan L. (American Economic Review, 2009)
This note responds to Christian Bayer (2009). Cooper and Willis (2004), hereafter CW, find the aggregate nonlinearities reported in Ricardo Caballero and Eduardo Engel (1993) and Caballero, Engel, and John Haltiwanger (1997) reflect mismeasurement of the employment gap, not nonlinearities in plant-level adjustment. Bayer concludes the CW result is not robust to alternative aggregate shock processes. We concur, but argue that the nonlinearity created by mismeasurement does not disappear. Instead, it is directly related to the level of the aggregate shock. The CW findings are robust for the natural case of unobserved gaps. (JEL E24, J23)